Book movement at Ukrainian prisoners’ of war Freistadt camp (Austro-Hungary) in 1915-1918 - Paliyenko Maryna; Sribniak Ihor (Рукописна та книжкова спадщина України, 2021)

(untitled)
The aim of the research. The article reconstructed the dynamics of the book movement at the Ukrainian prisoners’ of war (POWs) Freistadt camp (Austro-Hungary) during the First World War, as well as identified its influence on the formation of internees’ national self-consciousness. The research methodology includes the applicationof problem-oriented, chronological, historical, comparative, and retrospective researchmethods, the combination of which allows to provide fundamental insights into thepeculiarities of the book movement development at еру Freistadt camp. The scientificnovelty lies in recognizing the contribution of the Union for the Liberation of Ukraine(ULU) to the organizational process of the book movement at еру Freistadt camp, determining the sources of the camp library maintenance as well as defining the ULU’s rolein the Ukrainian camp community life. Conclusions. The article determined that Ukrainian books played a crucial role in the mission of Ukrainian POWs’ national self-consciousness formation at еру Freistadt camp. Hence, books effectively ‘accompanied’ theeducational activity at the camp, as POWs could deepen their acquired knowledgefrom educational courses by reading borrowed library books related to various sciences. Moreover, the library successfully performed informational functions, creating favorable conditions for POWs to get news in athenaeum to which fresh newspapers were regularly delivered. Thanks to the availability of prominent Ukrainian writers’, poets’,scholars’ and publicists’ writings at the Freistadt camp library, it empowered Ukrainian POWs to discover ‘new worlds’, enabling each educated internee to create his own image of Ukraine through self-education. By these means, Ukrainian prisoners of war became engaged in the active participation in the life of the Ukrainian camp community in Freistadt, being prepared well enough to rise in defense of their homeland duringthe Ukrainian War of Independence in 1917-1920.